Social construction of body image and weight loss behaviour among overweight adolescents / Suriati Sidek - Sidek, Suriati (Institute of Graduate Studies, UiTM, 2016)
Obesity among adolescents is often associated with body image dissatisfaction. However, very few studies have examined body image, as a social construct, among overweight adolescents in Malaysia, and the process by which such construction is perceived, experienced and reacted to through various social interactions. The literatures also show that body dissatisfaction may lead to disordered eating behaviour, as a means to improve physical appearance. Therefore, this phenomenological study that was guided by the social constructionism lens, aims to explore the construct of body image and weight loss behaviour among overweight adolescents. Thirty-three in-depth semi-structured interviews with 13 to 17 years old male and female overweight adolescents from an urban setting in Selangor were analysed using thematic analysis. The present study found that body image is conceptualised through perceptual, affective, cognitive and behavioural domains of overweight adolescents. Overweight adolescents perceived body attributes as more important than other physical characteristics. They described their body image as it is based on the appearance comments and criticism that they received from social interactions with peers and parents. Most of them wanted to be thin for social acceptance…